2015
DOI: 10.1111/bju.13110
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin (OnabotulinumtoxinA) in the male non‐neurogenic overactive bladder: clinical and quality of life outcomes

Abstract: ObjectiveTo assess the efficacy of OnabotulinumtoxinA (BTXA) injections in men with drug-refractory non-neurogenic overactive bladder (NNOAB). Patients and MethodsA total of 43 men received BTXA injections for NNOAB from 2004 to 2012. Patient Global Impression of Improvement (PGI-I) score was obtained. For men with wet NNOAB, change in number of pads per day was also assessed. ResultsForty-three men with a mean age of 69 (range 37-85) received at least one injection. Of the 43 men, 20 (47%) had prior prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…Lower CISC rates, in addition to the lower discontinuation rate for the RP subgroup, could mean that BoNT-A treatment is more tolerable for patients with prior RP (as is true for desobstructive surgery). This favourable outcome for the RP subgroup corresponds to the findings of Habashy et al [12], where patients who had undergone RP prior to BoNT-A treatment showed the greatest subjective improvement in urinary symptoms, as well as a statistically significant reduction in pad usage. Another study conducted by Rahnama'i et al [10] compared four subgroups: iOAB without surgery, neurogenic OAB, post-TURP OAB, and post-RP OAB.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lower CISC rates, in addition to the lower discontinuation rate for the RP subgroup, could mean that BoNT-A treatment is more tolerable for patients with prior RP (as is true for desobstructive surgery). This favourable outcome for the RP subgroup corresponds to the findings of Habashy et al [12], where patients who had undergone RP prior to BoNT-A treatment showed the greatest subjective improvement in urinary symptoms, as well as a statistically significant reduction in pad usage. Another study conducted by Rahnama'i et al [10] compared four subgroups: iOAB without surgery, neurogenic OAB, post-TURP OAB, and post-RP OAB.…”
Section: Discussionsupporting
confidence: 86%
“…Multiple studies suggest that several differences exist between iOAB subgroups, depending on whether the patients underwent prostate surgery prior to BoNT-A treatment. Habashy et al [12] studied clinical improvement in continence after BoNT-A treatment in three subgroups (no prostate surgery, TURP, and RP) and found a significant improvement only in the RP subgroup. In addition, even on a histopathological level, persistent detrusor overactivity following TURP seems to be associated with increased vascular resistance of the bladder vessels and decreased perfusion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Intravesical injection with BoNT-A is a well-established treatment for overactive bladder syndrome (8,9). Many studies focus on treatment efficacy and follow-up of patients who were successfully treated.…”
Section: Discussionmentioning
confidence: 99%
“…Habashy et al reported intravesical BoNT-A injection for 43 men with non-neurogenic OAB, including 20 (47%) who had prior prostate surgery, of whom 11 had RP and nine had TURP [ 25 ]. Men with a history of prior prostate surgery had similar Patients’ Global Impression of Improvement (PGI-I) scores to those without prior prostate surgery (2.6 ± 0.5 vs. 2.8 ± 0.5, respectively, p = 0.6).…”
Section: Prior Prostate Surgerymentioning
confidence: 99%
“…The authors concluded that intravesical BoNT-A injection in men with OAB symptoms that are refractory to oral medication can achieve significant symptom improvement despite a history of prior prostate surgery. Nonetheless, those with a history of prior RP benefited more than those with a history of prior TURP in both daily pad use and PGI-I score [ 25 ]. Considering AEs after intravesical BoNT-A injection, Kuo et al .…”
Section: Prior Prostate Surgerymentioning
confidence: 99%